Frequency of Temporomandibular Joint Disorder among Medical Students in Balochistan - Najeeb Ullah, Ahmed Jawad Khan, Fakira, Sadia Iqbal, Farhat Gul, Shehzaib Ejaz, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Temporomandibular disorders (TMDs) are a serious health issue among university students, especially in challenging study programs. Nonetheless, there is limited information regarding the prevalence of TMDs among dental and medical students in Balochistan. Methodology: The cross-sectional study evaluated 376 dental and medical students with Fonseca's Anamnestic Index. Data collection was conducted via a validated two-part questionnaire delivered via Google Forms. The first section examined possible risk factors such as age, gender, department of study, year of study, number of study hours per day and sleeping hours. The second section included Fonseca's Anamnestic Index, a 10-item test with known reliability (Cronbach's α=0.82) for screening TMD, which categorizes cases as no TMD (0-15 points), mild (20-40 points), moderate (45-65 points), or severe (70-100 points). SPSS version 21 was used to analyze statistical significance. Results: The prevalence of TMD was found to be 57.98% overall, with 26.86% mild, 20.48% moderate, and 10.64% severe. The most frequent symptoms were jaw mobility problems (22.6%), bruxism (22.9%), and headache (22.1%). Severe TMD cases had significantly longer study times (5.18±1.4 vs 3.89±1.2 hours/day, p<0.001) and shorter sleep time (7.55±1.4 vs 10.61±1.8 hours/night, p<0.001). Prevalence rose with academic year, being highest in fourth-year students (38.5%, p<0.001), with no significant gender (p=0.098) or field-of-study differences (p=0.212). Conclusion: The very high prevalence of TMD among Balochistan's medical and dental students indicates strong associations with academic workload and sleep deprivation. These results emphasize the necessity for institutional interventions in stress management and sleep hygiene in health professions education. Keywords: Temporomandibular disorders, academic stress, bruxism, medical students, dental students